Food preservation process design - Heldman, Dennis R. (Food science and technology international series, 2011)
The preservation processes for foods have evolved over several centuries. This work deals with the fate of food quality attributes during the preservation process, and the concept of optimizing the process parameters to maximize the retention of food quality